Analisis Nilai Tambah dan Efisiensi Usaha Tape Ketan pada Industri Rumah Tangga Tape Ketan di Desa Sungai Karias Kecamatan Amuntai Tengah Kabupaten Hulu Sungai Utara - Azwar Saihani; Siti Hapizah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2015)
The aim of this research is to determine the general description of home industry sticky tape seen from the characteristics of respondents and the views of the business production system, analyze the added value of sticky tape and analyze the efficiency of home industry sticky tape in Sungai Karias Village Amuntai Tengah District Hulu Sungai Utara Regency. Method research used is cencus method, the mothod of data collection uses interviews. Data collection was conducted from May until July 2015. The data analysis used is qualitative analysis to get general condition description of sticky tape industry processed descriptively. Quantitative analysis uses analysis of costs, revenues, profits, value-added and business efficiency analysis. Analysis tool of added value is Hayami method. The results of this study showed that the total cost incurred is Rp.170.018,-, the average of revenue home industry sticky tape in once process production is Rp.341.712,-, the profits is Rp.171.694,-, added value obtained based on calculation Hayami method that is Rp.15.574,7 per kilogram of raw materials glutinous rice or 51,83% of the production value, and efficiencies obtained 2,00 that means the home industry sticky tape is efficient because the value more than 1. R/C ratio of 2,00 that means every Rp.1,00 cost incurred in home industry sticky tape will provide revenue 2,00 times of costs that incurred.